Effect of QR Code-Mind Map Teaching Book on Students’ and Teachers’ Enviromental Awareness Characters - Yusra, Nelly; Sakilah, Sakilah; Nova, Theresia Lidya; Berlian, Mery; Shahali, Edy Hafizan Mohd (Journal of Natural Science and Integration, 2024)
This study aims to analyze and describe the environmental care attitudes of students, teachers, lecturers, and students after using QR Code-Mind Map-based textbooks on environmental topics. This study used a combined approach, namely the ADDIE development model which includes analysis, design, development, implementation, and evaluation, with a survey design. Data were collected through an online questionnaire involving 62 teachers (15 lecturers and 47 teachers) and 126 students (65 high school students and 61 university students) from various institutions in Pekanbaru. Data analysis was conducted using descriptive-quantitative techniques and the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that the average score of environmental care attitude of lecturers was 90% with a good category, while students reached 89.5% with a good category. In addition, the criteria for the effectiveness of QR Code-Mind Map-based coursebooks in improving the Environmental Care Character of students and teachers showed 100% with the category “Very Good.” Thus, it can be concluded that this textbook is very effective in increasing awareness of environmental care and can be used as a guide and disseminated to be widely implemented by stakeholders. The QR Code-Mind Map-based textbooks on environmental topics will provide a good understanding, a good understanding will result in a good attitude towards the environment so that it can make characters us rahmatan lil alamin.Keywords: teaching book, effectiveness, qr code-mind map, environmental awareness characters